Enhancing the Image of Bajo Village Settlement Areas through Amphibious House - Setiadi, Ahsan Hidayat; Syah, Andi Al Mustagfir; Nahdatunnisa (Syntax Corporation, 2025)
Coastal communities like the Bajo people in Tiworo Tengah District, West Muna Regency, face increasing environmental challenges due to climate change and rising sea levels. The traditional stilt houses they inhabit are becoming inadequate in adapting to these conditions, negatively affecting the settlement's functionality and image. This research aims to enhance the image of the Bajo settlement area by introducing the concept of the amphibious house. This dwelling design can float during flooding and return to its base when water recedes. This study employs a qualitative descriptive method with a rationalistic architectural approach, incorporating field observations, documentation, interviews, and literature studies. The research focuses on the settlement's spatial, physical, and visual aspects to identify the existing conditions and the potential for improvement. The findings reveal that the current Bajo settlement lacks adaptation to environmental dynamics and exhibits a declining aesthetic and functional image. The amphibious house concept offers a culturally sensitive and environmentally adaptive solution that aligns with the socio-economic conditions and traditions of the Bajo community. The integration of amphibious structures enhances the livability, safety, and visual appeal of the settlement while preserving the unique maritime identity of the Bajo people. This research implies that combining vernacular architecture with innovative, adaptive design strategies can effectively address environmental vulnerability in coastal communities, offering a sustainable solution for similar contexts across Indonesia and beyond.